PENGARUH KECERDASAN EMOSIONAL DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA SERTA IMPLIKASINYA PADA KINERJA PEGAWAI - Noviantoro, Djatmiko; Jeanita, Kurnia Dwi; Suyantiningsih, Tri (Forum Bisnis Kewirausahaan, 2024)
Abstract:. This research aims to determine and prove the influence of emotional intelligence and the work environment on work productivity and its implications for the performance of employees at the Uptb Samsat Banyuasin II Bapenda, South Sumatra Province. The research methodology employed in this study is quantitative research, utilizing a descriptive-correlational research design. The research analysis method utilizes Structural Equation Modeling (SEM).Based on the data analysis , it can be concluded that there is an influence of Emotional Intelligence on the Work Productivity of employees. There is also an impact of the Work Environment on the Work Productivity of employees at Samsat Banyuasin II Bapenda South Sumatra Province. Furthermore, there is an influence of Emotional Intelligence on the Performance of employees at Samsat Banyuasin II Bapenda South Sumatra Province, as well as an impact of the Work Environment on the Performance of employees at Samsat Banyuasin II Bapenda South Sumatra Province. Lastly, there is an influence of Work Productivity on the Performance of employees at Samsat Banyuasin II Bapenda South Sumatra Province. Keywords: Emotional Intelligence, Work Environment, Work Productivity, Employee Performance